More Games and Giggles Wild About Animals - Wall, Ryan Jeanette (Pleasant Company Publications, 1998)
Includes an assortment of wordsearches, crossword puzzles, and word games, tricks, mazes, number games, and more.
Keywords: Amusements; Games for girls